A study of the need for an independent judicial nomination commission in Malaysia / Anati Kisahi, Farah Juliana Mohamad Anuar and Sharifah Razali - Kisahi, Anati; Mohamad Anuar, Farah Juliana; Razali, Sharifah (2008)
This paper is basically a study that determines the need to have a constitutional reform in order to establish an independent Judicial Nomination Commission in Malaysia. As stated in Chapter One, this study is conducted due to the great criticisms leveled against the present judiciary as well as the judicial appointment system. Therefore, the need to establish the independent Judicial Nomination Commission is measured by analyzing whether or not the present judiciary as well as the judicial appointment system provided by Article 122B of the Federal Constitution is in fact muddled with problems. All the quandaries have been laid down in Chapter Two of this paper and it is submitted that the judiciary and the present system of judicial appointments are cluttered with problems that range from politicized judicial appointment, non credible judges, backlog cases and even extends to great failure to write judgments and deferred. Chapter Three examines the models of independent judicial appointment commission of other countries such as the Judicial Appointments Commission of England and Wales, Northern Ireland Judicial Appointments Commission, Judicial Appointments Board for Scotland and South African Judicial Service Commission while the feasibility of adopting such models are concluded in Chapter Four of the paper. It is submitted that there is none of the models that can be adopted as a whole. In order to ensure the effectiveness of the proposed independent Judicial Nomination Commission, it is observed that it needs to be a mixture of the featured examined models.